A New Shot Boundary Detection Approach Based Motion Estimation of MPEG-4 - Gang Zhang; Wenlong Wang; Xiaoyan Kuang; Yue Niu (2009 International Conference on Management and Service Science, 2009)
Shot boundary detection is the first step of video retrieval. In this paper we propose a new approach to detecting shot boundary based on motion estimation for uncompressed video, we firstly give an overview of existing algorithms, then we explain our algorithm in detail, our method is used in fire fighting command and record system for fire fighting agency. This algorithm proposes the concept of frame comparison and the adaptive threshold and has better performance than the traditional approaches. At last, we give the experiment results and conclusion.